TANTANGAN BARU BAGI HUKUM HUMANITER INTERNASIONAL DALAM MENGHADAPI ANCAMAN HIBRIDA DAN KONFLIK ASIMETRIS - Firman Gunawan; Erick Sartani Marbun, Tarsisius Susilo, Budiman Marpaung, Budi Saroso (INTELIGENSIA MEDIA, 2025)
Modern armed conflicts have evolved far from conventional state-on-state wars into complex, “hybrid” forms. They often involve non-state actors and advanced technologies (cyber, drones, long-range weapons), as well as mixed strategies that combine military force, cyber operations, information campaigns, and proxy fighters. This article analyzes the implications of these changing conflict characteristics for International Humanitarian Law (IHL). The study uses normative-analytical methods and case studies focusing on global events (Gaza, Syria, Ukraine) and the conflict in Papua. The analysis finds that while the existing IHL framework (the 1949 Geneva Conventions and customary law) still applies when the criteria of an armed conflict are met, its enforcement faces serious challenges. Cyber attacks and propaganda, for example, are not always clearly classified as armed conflict, and proxy or non- state combatants often violate IHL core rules with impunity. Cases like Gaza and Syria show major violations by both state forces and non-state armed groups, whereas Russia’s strategy in Ukraine employs a multi-domain “hybrid” approach with extensive attacks on civilian infrastructure. In Papua, separatist armed actions and domestic information operations (including coordinated pro-government social media campaigns) highlight hybrid aspects in the local context. We hypothesize that while IHL remains relevant, it requires adaptive interpretation and enforcement to be effective in the hybrid era. This study contributes an Indonesian military perspective that emphasizes sovereignty and civilian protection, and offers policy recommendations—such as enhanced IHL training for forces, military SOPs grounded in IHL, and stronger national legal frameworks—to meet modern threats.